A Hoard of Military Awards, Jewellery and Coins from Colchester. (11th February 2016) - Crummy, Nina; Henig, Martin; Ward, Courtney
Abstract: A hoard of objects found at the early Roman colony at Colchester in a small hole scraped into the floor of a house destroyed during the Boudican revolt includes a group of high-quality gold jewellery, three silver military awards, a bag of coins, an unusual silver-clad wooden box and other items. Buried in haste as the British approached, they provide a remarkably clear image of one couple's background, achievements, taste and social standing. A bulla shows that the man was a Roman citizen, the awards that he was a veteran soldier of some distinction, while parallels for the woman's jewellery suggest that it was acquired in Italy.